COMPETITIVENESS AND MARKET REORIENTATION IN MOLDOVA’S AGRI-FOOD EXPORTS TO THE EUROPEAN UNION - Cimpoies, Liliana; Stoianoglo, Corina (Economics of Agriculture, 2026)
This paper examines how Moldova’s trade in agricultural and food products has changed between 2013 and 2024, against the background of closer economic integration with the European Union (EU). The analysis covers 24 agri-food product groups, including both agricultural commodities and processed foods, using official data from the National Bureau of Statistics and a set of standard trade competitiveness indicators. The results reveal uneven patterns of competitiveness across product groups. While sectors such as meat, fish, and dairy continue to face structural weaknesses, products like cereals, oilseeds, fats and oils, and beverages retain strong competitive positions and positive trade balances. Trade in processed food products shows a moderate but gradually increasing level of intra-industry exchange, suggesting slow and uneven upgrading. Research results underline a continuing transformation of Moldova’s agri-food trade and highlight the importance of targeted policies to strengthen competitiveness, diversify exports, and support deeper integration into EU value chains in a context of increased global uncertainty.